Społeczno-kulturowe aspekty adopcji w Boliwii - Ziółkowska-Kuflińska, Magdalena (Wydawnictwo Naukowe UAM, 2007)
The principal aim of this article is to determine the function of the adoption in Bolivia, which usually is the main cultural and social value. I am of the opinion that the adoption in Bolivia cannot be considered in isolation from the cultural, social and historical determination. I also consider that interpretation and analysis of the conditions of adoption should be considered with a lot of relations between the members of this society. Adoption in Bolivia is a lengthy and complex process and the Bolivian judicial and administrative requirements are numerous. Although adoption of children in Bolivia by foreigners remains a sensitive issue, the Bolivian courts are willing to approve such adoptions. Bolivia has two types of adoptions: national and intercountry. However, Bolivia does not allow intercountry adoptions to countries that have not ratified the Hague Convention on Intercountry Adoption, including the United States. In order to be eligible for adoption, a Bolivian child must be "abandoned." Abandonment is a legal finding made by the Bolivian court, and must occur before the child is assigned to prospective adoptive parents. In effect, this prohibits so-called "direct" adoptions, in which the birth parent gives a child directly (or via an intermediary) to specific prospective adoptive parents for adoption. In addition, this effectively bars adoptive parents from searching for and locating a child on their own. Prospective adoptive parents must work with the Vice-Ministry of Gender and Generational Affairs to locate a child that is eligible for adoption. Adoption in Bolivia has a very important value to all members of this country. This problem is fundamental from the society's point of view and it is very important to observe the development and solutions of this question.
Social and cultural aspects of adoption in Bolivia